2020
DOI: 10.1002/pd.5855
|View full text |Cite
|
Sign up to set email alerts
|

Dimensionless squared jerk: An objective differential to assess experienced and novice probe movement in obstetric ultrasound

Abstract: Objective: Widely accepted, validated and objective measures of ultrasound competency have not been established for clinical practice. Outcomes of training curricula are often based on arbitrary thresholds, such as the number of clinical cases completed. We aimed to define metrics against which competency could be measured. Method: We undertook a prospective, observational study of obstetric sonographers at a UK University Teaching Hospital. Participants were either experienced in fetal ultrasound (n = 10, >20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…A comparison between experienced sonographers and novice operator was made by Dromey et al but in an experimental setting. 17 They analyzed the difference in deliberate hand movements using a mid-trimester phantom and showed that experienced sonographers reached the desirable plane easier than non-experienced sonographers and in a shorter time. A prospective cohort study investigated the performance of trainees compared to specialists in third-trimester ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison between experienced sonographers and novice operator was made by Dromey et al but in an experimental setting. 17 They analyzed the difference in deliberate hand movements using a mid-trimester phantom and showed that experienced sonographers reached the desirable plane easier than non-experienced sonographers and in a shorter time. A prospective cohort study investigated the performance of trainees compared to specialists in third-trimester ultrasound.…”
Section: Discussionmentioning
confidence: 99%
“…Common SPs include the trans-ventricular plane to measure the fetal head circumference, the trans-abdominal plane to measure the fetal abdominal circumference, and femoral plane to measure the femur length. Obtaining manual measurements can be time-consuming and operator-dependent, especially for trainees [9], and results in high inter-and intra-operator variability [13]. In fetal biometry, interoperator measurements variability range between ±4.9% and ±11.1% and an intra-operator variability between ±3% and ±6.6% [19].…”
Section: Introductionmentioning
confidence: 99%
“…There is little global consensus on how to train, assess and evaluate skills in prenatal second trimester ultrasound (US) screening. Recommended assessment and quality control metrics vary across countries and institutions [5]. Despite this, standardized US planes and metrics to assess fetal size are well established [20].…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of these standard planes is subject to intraoperator and interoperator variabilities [22] which introduces some degree of uncertainty in the clinically obtained weight measurements and consequently requires a degree of caution when clinicians are interpreting fetal growth reports. Sonography expertise has a significant impact on minimizing variability of image quality and fetal biometry [5]. Consequently, training and competence assessment are of great importance to ensure effective, reproducible and safe clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation